Light-generated oligonucleotide arrays for rapid DNA sequence analysis. - Pease, A C (1994)
In many areas of molecular biology there is a need to rapidly extract and analyze genetic information; however, current technologies for DNA sequence analysis are slow and labor intensive. We report here how modern photolithographic techniques can be used to facilitate sequence analysis by generating miniaturized arrays of densely packed oligonucleotide probes. These probe arrays, or DNA chips, can then be applied to parallel DNA hybridization analysis, directly yielding sequence information. In a preliminary experiment, a 1.28 x 1.28 cm array of 256 different octanucleotides was produced in 16 chemical reaction cycles, requiring 4 hr to complete. The hybridization pattern of fluorescently labeled oligonucleotide targets was then detected by epifluorescence microscopy. The fluorescence signals from complementary probes were 5-35 times stronger than those with single or double base-pair hybridization mismatches, demonstrating specificity in the identification of complementary sequences. This method should prove to be a powerful tool for rapid investigations in human genetics and diagnostics, pathogen detection, and DNA molecular recognition.